Designing immunogenic nanotherapeutics for photothermal-triggered immunotherapy involving reprogramming immunosuppression and activating systemic antitumor responses. (October 2020) - Wang, Jing; Chang, Yanzhou; Luo, Hui; Jiang, Wenxiao; Xu, Ligeng; Chen, Tianfeng; Zhu, Xueqiong
Abstract: Low tumor mutational burden and absence of T cells within the tumor sites are typical characteristics of "cold immune tumors" that paralyzes the immune system. The strategy of reversing "cold tumors" to "hot tumors" infiltrated high degree of T cells in order to activate anti-tumor immunity has attracted lots of attentions. Herein, immunogenic core–shell Au@Se NPs is fabricated by gold-selenium coordination bond to realize nanoparticles-mediated local photothermal-triggered immunotherapy. As expected, incorporation of gold nanostars (AuNSs) with improved photothermal stability and conversion efficiency promotes the disintegration and transformation of selenium nanoparticles (SeNPs), thus leading to enhanced cancer cells apoptosis by producing higher hyperthermia. Moreover, the results of in vivo experiments demonstrate that the synergy between SeNPs-mediated chemotherapy and AuNSs-induced photothermal therapy not only generated a localized antitumor-immune response with excellent cancer killing effect under the presence of tumor-associated antigens, but also effectively reprogrammed the tumor associated macrophages (TAMs) from M2 to M1 phenotype with tumoricidal activity to devour distant tumors. Without a doubt, this study not only provides a potent strategy to reverse the immunosuppressive tumor microenvironment, but also offers a new insight for potential clinical application in tumor immunotherapy. Graphical abstract: The present study provides demonstration of rational design of immunogenic nanotherapeutics Au@Se NPs for PTT-triggered immunotherapy involving reprogramming immunosuppression and activating systemic antitumor responses, which offers a new insight for potential clinical application in tumor immunotherapy. Image 1